Konstitusionalitas Penundaan Pemilihan Umum di Indonesia - Rizki AD, Andi Muh. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Institut Agama Islam Negeri Sultan Amai Gorontalo, 2024)
General elections as a means of popular sovereignty have been explicitly described in legislation. This paper examines the postponement of general elections by the President through Presidential Regulation in Lieu of Law. The writing is done by using descriptive normative legal research method that uses some primary materials and secondary data supported by tertiary legal materials and analysed qualitatively. In addition, the research method used is a comparative approach to several countries that regulate and have postponed elections in their countries. Based on the results of this research, it is known that if the postponement of general elections is carried out at this time by the State of Indonesia, then it is irrelevant and contrary to constitutional democracy. This is because constitutional democracy emphasises the sovereignty of the people based on the constitution. In addition, the norms in the current Indonesian constitution do not provide an opportunity to postpone elections. If there is still a postponement of general elections without changing the constitution, it is clearly contrary to constitutional democracy.